Stomalı yetişkin bireylerde uyku hijyeni eğitimi ve lavanta yağı inhalasyonunun uyku kalitesi, yorgunluk ve sağlıkla ilişkili yaşam kalitesine etkisi - Koca, Rabia (My University, 2024)
Amaç: Stomalı yetişkin bireylerde uyku hijyeni eğitimi ve lavanta yağı inhalasyonunun tek başına ve birlikte uygulanmasının uyku kalitesi, yorgunluk ve yaşam kalitesi üzerindeki etkisini araştırmaktır. Gereç ve Yöntem: Randomize kontrollü türdeki bu çalışma,T.C. İstanbul İl Sağlık Müdürlüğü’ne bağlı bir Şehir Hastanesinin Genel Cerrahi ve Üroloji kliniklerinde 14.06.2022-27.10.2023 tarihleri arasındastoma cerrahisi üzerinden en az üç ay geçmiş olan 106 stomalı birey ile yapıldı.Örneklemi; Grup 1’deuykuhijyeni eğitimi ilebirlikte lavanta yağı inhalasyonu uygulanan (n=25),Grup 2’de sadece uyku hijyeni eğitimi uygulanan(n=26),Grup 3’te sadece lavanta yağı inhalasyonu uygulanan (n=27) ve Grup 4’te hiçbir müdahaleuygulanmayan kontrol grubu (n=28)stomalı bireyler oluşturdu. Veriler “Tanıtıcı Özellikler Formu”, “Pittsburgh Uyku KalitesiÖlçeği”, “Chalder Yorgunluk Ölçeği”, “Stoma Yaşam Kalitesi Ölçeği” aracılığıyla toplandı. Veriler, tanımlayıcı istatistiksel yöntemler, Tek Yönlü Varyans Analizi, Kruskal-Wallis testi, post-hoc testler ilr değerlendirildi. Bulgular:Katılımcıların yaş ortalaması 59,05±9,99 ve %59,4’ü erkekti. Grupların bireysel, uyku düzeni ve stoma ile ilgili özellikleri benzerdi.Çalışmada, uygulanan üç farklı girişim öncesi grupların uyku kalitesinin kötü, yorgunluk ve yaşam kalitesinin orta düzeyde olduğu bulundu. Bir ay düzenli tek başına ve birlikte uygulananuyku hijyeni eğitimi ve lavanta yağı inhalasyonu sonrasıstomalı bireylerin uyku kalitesinin arttığı, yorgunluğun azaldığı ve sağlıkla ilgili yaşam kalitesininiyileştiği görüldü. Sonuç:Mevcut çalışma bulguları stomalı bireylerin uyku kalitesi, yorgunluk ve yaşam kalitesindeki iyileşmenin en fazla uyku hijyeni eğitimi ile birlikte lavanta yağı inhalasyonu uygulanan grupta olduğunu ve bunu tek başına lavanta yağı inhalasyonu uygulanan grubun izlediğini gösterdi.

Objective: To investigate the effects of sleep hygiene education and lavender oil inhalation, alone and in combination, on sleep quality, fatigue, and health-related quality of life in adults with an ostomy. Materials and Methods: This randomized controlled trial was conducted between June 14, 2022, and October 27, 2023, with 106 individuals who had undergone ostomy surgery at least three months prior at the general surgery and urology clinics of a city hospital affiliated with the Republic of Turkey Istanbul Provincial Health Directorate. The sample was divided into four groups: Group 1 received both sleep hygiene education and lavender oil inhalation (n=25), Group 2 received sleep hygiene education alone (n=26), Group 3 received lavender oil inhalation alone (n=27), and Group 4 was the control group that received no intervention (n=28).Data were collected using a demographic characteristics form, the Pittsburgh Sleep Quality Index, the Chalder Fatigue Scale, and the Stoma Quality of Life Scale. Data analysis was performed using descriptive statistical methods, one-way analysis of variance, the Kruskal-Wallis test, and post-hoc tests. Results:The mean age of the participants was 59.05±9.99 years, and 59.4% were male. The groups had similar individual, sleep pattern, and stoma-related characteristics. Before the interventions, the sleep quality of the groups was poor, while fatigue and quality of life were at moderate levels. After one month of regular intervention, it was determined that sleep hygiene education and lavender oil inhalation, both alone and in combination, improved sleep quality, reduced fatigue, and enhanced health-related quality of life in individuals with an ostomy. Conclusion: The findings of this study indicate that the greatest improvement in sleep quality, fatigue, and quality of life in individuals with an ostomy was observed in the group that received both sleep hygiene education and lavender oil inhalation, followed by the group that received lavender oil inhalation alone.
Effects of sleep hygiene education and lavender oil inhalation on sleep quality, fatigue, and health-related quality of life in adults with an ostomy
Keywords: fatigue; health-related quality of life; Insomnia; lavanta yağı inhalasyonu; lavender oil inhalation; Ostomy; sağlıkla ilişkili yaşam kalitesi; Sleep; Sleep disorders; sleep hygiene education; sleep quality; Stoma; Uyku; Uyku bozuklukları; uyku hijyeni eğitimi; uyku kalitesi; Uykusuzluk; yorgunluk